Application of the flowing solution culture techniques to studies involving mycorrhizas - Howeler, Reinhardt H.; Edwards, D.; Asher, CJ (Springer, 1981)
A technique to study mycorrhizal effects on growth and P-uptake of cassava (Manihot escultenta, Crantz) grown in flowing solution culture is described. Phosphorus concentrations were carefully maintained constant at 0.1, 1, 10 and 100 ?M by daily analyses and adjustment of the nutrient solutions. Inoculation with mycorrhizal roots hada positiveeffect on P content of plant tissue and/or plant growth only at the two lowest P-concentrations in soulution. These concentrations are two to three orders of magnitude lower than those normally used in conventional nutrient solution cultures.